(untitled) (Journal of the College of Basic Education, 2026)
This study aims to examine contemporary trends in industrial design by analyzing the aesthetic approaches and functional standards adopted by designers in the development of industrial products, with a focus on the relationship between form, function, and meaning in contemporary design. The research adopts a descriptive–analytical methodology, grounded in a theoretical framework that explains the evolution of aesthetic and functional concepts in industrial design, which is then applied practically through a comparative visual analysis of selected design samples representing different historical periods. The study is structured into a theoretical introduction, analytical axes outlining aesthetic and functional foundations, followed by a comparative applied analysis of models from the past and the present, leading to results that identify the most significant transformations in contemporary design thinking. The findings indicate that modern industrial design is based on achieving a conscious balance between visual appeal and functional efficiency, while considering user experience and technological advancements, thereby enhancing the quality of industrial products and their ability to respond to the demands of the modern era.